Handbook on Optimal Growth 1 Discrete Time - Dana, Rose-Anne; Van, Cuong; Mitra, Tapan; Nishimura, Kazuo (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The problem of efficient or optimal allocation of resources is a fundamental concern of economic analysis. The theory of optimal economic growth can be viewed as an aspect of this central theme, which emphasizes in general the issues arising in the allocation of resources over an infinite time horizon, and in particular the consumption-investment decision process in models in which there is no natural "terminal date". This broad scope of "optimal growth theory" is one which has evolved over time, as economists have discovered new interpretations of its central results, as well as new applications of its basic methods. The Handbook on Optimal Growth provides surveys of significant results of the theory of optimal growth, as well as the techniques of dynamic optimization theory on which they are based. Armed with the results and methods of this theory, a researcher will be in an advantageous position to apply these versatile methods of analysis to new issues in the area of dynamic economics. .